Tarok young people's speech. (6th December 2015) - Blench, Roger; Longtau, Selbut
Abstract : The paper describes the distinctive lexical and grammatical inventory of young people in Tarok, a Plateau language of East-Central Nigeria. Typical features are manipulation of the existing lexicon through both shortening and syllable insertion, conservation of archaic pronunciation, idiosyncratic sound shifts, arbitrary pronoun substitution, tonal changes, neutralization of noun class plurals, and sound shift in particles.